Metatranscriptomic analysis of the gut virome in Muscovy ducks reveals a novel duck reovirus potentially associated with hepatic and splenic hemorrhage - Liu, Chuang; Kang, Qixiang; Wang, Xuanci; Zeng, Fangui; Huang, Yihui; Yang, Yiqin; Geng, Rui; Liao, Jiamin; Luo, Xin; Yan, Zhuanqiang; Yin, Lijuan; Cao, Sheng; et al. (Frontiers in Immunology, 2025)
IntroductionDucks rank among the most important sources of animal protein globally, yet hepatic and splenic hemorrhage and necrosis in Muscovy ducks present a critical challenge to the poultry industry. The causes behind such diseases are often multifaceted, involving both established and newly emerging pathogens. MethodsIn this study, we leveraged metatranscriptomic sequencing to profile the intestinal viral communities of healthy and diseased Muscovy ducks from a Guangdong Province farm that experienced a hepatic and splenic hemorrhage in June 2024. ResultsOur findings revealed marked differences in viral community profiles between the two groups, with the diseased cohort exhibiting higher α-diversity. Taxonomic analyses across multiple levels uncovered significant variations in viral composition, including shifts in phylums like Uroviricota and families such as Demerecviridae. At the genus and species levels, several bacteriophages and eukaryotic viruses displayed differential abundance. Notably, Avian orthoreovirus was detected exclusively in diseased ducks, with a specific novel duck reovirus (NDRV) validated via RT-qPCR as a potential contributor to hepatic and splenic pathogenesis. In contrast, known pathogens such as Duck hepatitis A virus (DHAV) and Fowl adenovirus serotype 4 (FAdV-4) were not detected. DiscussionThis study constitutes the first comprehensive analysis of the Muscovy duck gut virome, highlighting NDRV as a potential causative agent and emphasizing the utility of metatranscriptomics in pathogen discovery.